Sub-Clinical Regional Macular Changes in Self-Reported Diabetic Subjects: Vascular and Retinal Layer Analysis Using Swept-Source OCT - Challa NK; Alghamdi WM; Alluwimi MS; Alshammeri S (Diabetes, Metabolic Syndrome and Obesity)
Naveen Kumar Challa, Waleed M Alghamdi, Muhammed S Alluwimi, Saleh Alshammeri Department of Optometry, College of Applied Medical Sciences, Qassim University, Buraidah, AlQassim, Saudi ArabiaCorrespondence: Naveen Kumar Challa, Department of Optometry, College of Applied Medical Sciences, Qassim University, Buraidah, AlQassim, Saudi Arabia, Tel +966531177518, Email N.challa@qu.edu.saAim: To assess and compare subclinical alterations in superficial capillary plexus vessel density (SCPVD) and retinal layers thickness in the macular region between individuals with type 2 diabetes mellitus (DM) and healthy controls.Methods: Swept-source OCT images were obtained from 29 control subjects and 24 diabetic subjects. Macular thickness (MT), retinal nerve fiber layer (RNFL) thickness, and ganglion cell layer (GCL) thickness were measured in the central macula and four quadrants of macular region using a 6.0 × 6.0 mm radial macular scan centered on the fovea. OCTA acquisition included a 3.0 × 3.0 mm macular scan for the foveal avascular zone (FAZ) and a 4.5 × 4.5 mm macular scan for SCPVD. The FAZ was manually mapped at the SCP on OCTA images.Results: In diabetic subjects, the superficial capillary plexus vessel density (SCPVD) was significantly lower in both the central (P = 0.04) and inferior (P = 0.01) regions compared to the control group. Additionally, diabetic patients showed a significant reduction in temporal macular thickness (MT) and thinning of the ganglion cell layer (GCL) in all three quadrants except in the central and inferior macula (P < 0.05). There was also significant thinning of the superior macular retinal nerve fiber layer (RNFL) in diabetics compared to controls (P = 0.02). While the foveal avascular zone (FAZ) was larger in diabetic subjects, this difference was not statistically significant (P = 0.78). Duration of diabetes has shown a significantly high positive correlation (r = 0.77, P < 0.01) with superior macular VD.Conclusion: The findings of this study suggest that the diabetic macula experiences significant ganglion cell layer (GCL) thinning and reduced superficial capillary plexus (SCP) vascular density even before the onset of clinical retinopathy. Swept-source OCT proves to be an essential tool for detecting these early changes in diabetic patients.Keywords: tomography, age, RNFL, SCPVD, FAZ, diabetes mellitus